2022
DOI: 10.1111/apt.17264
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and T cell‐associated responses to SARS‐CoV‐2 immunisation in gut inflammation (STAR SIGN study): effects of biologics on vaccination efficacy of the third dose of mRNA vaccines against SARS‐CoV‐2

Abstract: Background: Immunosuppressed patients with inflammatory bowel disease (IBD) experience increased risk of vaccine-preventable diseases such as COVID-19. Aims: To assess humoral and cellular immune responses following SARS-CoV-2 booster vaccination in immunosuppressed IBD patients and healthy controls. Methods: In this prospective, multicentre, case-control study, 139 IBD patients treated with biologics and 110 healthy controls were recruited. Serum anti-SARS-CoV-2 spike IgG concentrations were measured 2-16 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 64 publications
(195 reference statements)
2
11
0
Order By: Relevance
“…STAR SIGN (Systemic and T cell-Associated Responses to SARS-CoV-2 booster Immunisation in Gut iNflammation) is a national multi-centre case-control study investigating the impact of biologic treatment in patients with IBD on immunogenicity towards SARS-CoV-2 vaccination. 13 It is designed as an observational trial combining prospective data from patient questionnaires and blood sample analysis with retrospective data collected manually from electronic medical records. The study protocol received approval by the Ethics Committee of Eastern Switzerland under the project-ID 2021-02511.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…STAR SIGN (Systemic and T cell-Associated Responses to SARS-CoV-2 booster Immunisation in Gut iNflammation) is a national multi-centre case-control study investigating the impact of biologic treatment in patients with IBD on immunogenicity towards SARS-CoV-2 vaccination. 13 It is designed as an observational trial combining prospective data from patient questionnaires and blood sample analysis with retrospective data collected manually from electronic medical records. The study protocol received approval by the Ethics Committee of Eastern Switzerland under the project-ID 2021-02511.…”
Section: Methodsmentioning
confidence: 99%
“…9,10,12 Recently, we and others demonstrated that impaired immune responses in anti-TNF-treated patients with IBD manifest even after a third dose of SARS-CoV-2 mRNA vaccines. [13][14][15][16] This impaired humoral vaccine response correlates with a higher rate of SARS-CoV-2 breakthrough infections in anti-TNF-treated patients with IBD, highlighting the increased risk faced by these patients. 15,17 Vaccination with a fourth dose of omicron-adapted bivalent vaccines can protect from severe COVID-19 and is recommended for at risk immunosuppressed patients including anti-TNF-treated patients with IBD.…”
Section: Introductionmentioning
confidence: 98%
“… 8 Likewise, two other studies reported reduced IFN-γ secretion in vaccinated patients treated with TNF antagonists, whereas those not treated with TNF antagonists had T-cell responses similar to controls without IBD. 9 , 10 These observations could be explained by a potential reduction in T-cell functionality or specificity in the absence of quantitative alterations in relevant T-cell subsets. As such, a comprehensive appraisal of qualitative T-cell responses, neutralising antibody responses, and the risk of breakthrough infections deserves attention in future studies, assessing which domains are most relevant for guiding vaccination prioritisation in patients with IBD receiving immunomodulating treatment.…”
mentioning
confidence: 99%
“…Woelfel and colleagues examined the impact of biologics on humoral and T‐cell associated responses to the third dose of an mRNA SARS‐CoV‐2 vaccine among 139 patients with IBD on biologics (81 on tumour necrosis factor α antagonists [anti‐TNF], 58 treated with vedolizumab or ustekinumab) and 110 controls. 1 Humoral immune responses were quantified by anti‐spike protein IgG concentrations. Cellular immunity was defined by T‐cell‐mediated interferon‐γ release after stimulation of whole blood with SARS‐CoV‐2 antigens.…”
mentioning
confidence: 99%
“…With the coronavirus pandemic waning but still very much present, whether the degree of protection conferred by the SARS‐CoV‐2 vaccines is similar to those on immunosuppression remains unclear. Woelfel and colleagues examined the impact of biologics on humoral and T‐cell associated responses to the third dose of an mRNA SARS‐CoV‐2 vaccine among 139 patients with IBD on biologics (81 on tumour necrosis factor α antagonists [anti‐TNF], 58 treated with vedolizumab or ustekinumab) and 110 controls 1 . Humoral immune responses were quantified by anti‐spike protein IgG concentrations.…”
mentioning
confidence: 99%